Pengaruh Latar Belakang Pendidikan, Lama Kerja, dan Budaya Organisasi terhadap Kinerja Pegawai pada Pemerintah Kabupaten Tapanuli Tengah - Aprinus Saragih (Neolectura, 2021)
This study aims to analyze the effect of educational background, length of work and organizational culture on employee performance. Central Tapanuli Regency Government. The formulation of the problem in this study is whether educational background, length of work and organizational culture affect the performance of employees in the Central Tapanuli Regency Government. The design of this study is a quantitative study using 92 samples, where the data were analyzed using the Partial Least Square (PLS) technique with the help of Smart PLS software. The results showed that the three independent variables used in this study, namely the educational background of employees, organizational culture and length of work had a positive and significant effect on employee performance in the government of Central Tapanuli Regency by 82.5% while the remaining 17.5% was influenced by factors other variables not used in this study.